Japanese contractor's approaches in managing design and build contract in Singapore - Toh, Boo Hor. (2008)
The objective of this report is to examine the approach of a famous international Japanese contractor Obayashi in managing a design and build contract in Singapore. The method of cost control, the management of construction schedule, co-ordination between the consultatn and sub-contractors and the quality control methods to achieve the owner's requirements will be clearly described.